Spatialization of saturated hydraulic conductivity using the Bayesian Maximum Entropy method: Application to wastewater infiltration areas. (1st October 2021) - Rabouli, Sara; Serre, Marc; Dubois, Vivien; Gance, Julien; Henine, Hocine; Molle, Pascal; Truffert, Catherine; Delgado-Gonzalez, Laura; Clément, Rémi
Highlights: Electrical Resistivity Tomography (ERT) is able to characterize soil heterogeneity. Bayesian Maximum Entropy (BME) integrates 2D ERT and localized infiltration data. BME data fusion results in accurate 2D fields of hydraulic conductivity (Ks). Accurate 2D Ks fields optimize the design for treated wastewater infiltration. Abstract: Wastewater treatment, a major issue at the European level, focuses on improving surface water and groundwater quality, preserving the receiving environment, and ensuring a sustainable use of water. Soil infiltration is increasingly practiced downstream of wastewater treatment plants, particularly in rural areas without surface water bodies, as is the use of soil as an additional buffer and treatment step. However, the design of infiltration areas on heterogeneous soils remains an extremely complex task due to the costly and time-consuming spatial measurement of saturated hydraulic conductivity (Ks). This article proposes integrating 2D electrical resistivity tomography and infiltration tests into a Bayesian Maximum Entropy method, yielding a vertical mapping of soil heterogeneities at a metric scale. This updated method will facilitate infiltration area design in a heterogeneous soil setting. Graphical abstract: Image, graphical abstract